firesong: book three in the wind of fire trilogy - Nicholson, William; William Nicholson (United Kingdom Hyperion paperbacks, 2002)
have saved their family and the rest of the people from slavery and helped bring about the downfall of the cruel city- state of the mastery. Now, led by their mother, a prophetess, they are free to seek their promised land. But the journey is long and hard, filled with many dangers, enemies, and temptations. And each of the travelers is preoccupied with his or her own worries. Hanno Hath, the twins' father is troubled his beloved wife weakens as they draw closer to the promised land. Also, he must bolster the endurance of the often doubting and disgruntled Manth people. Bowman is torn between his attraction to Sisi, a former princess, and the destiny he believes to be inevitable to sacrifice himself for the good of his people. Kestrel too feels a pull toward a mission but for some reason, she cannot envision her life beyond the journey.
English